Styles of Discussion: Online Facilitation Factors - Sackville, Andrew; Sherratt, Cathy (Proceedings of the International Conference on Networked Learning, 2006)
Whilst tutoring a supported online programme in Clinical Education over the last six years, we have become aware that there are significant differences in the ways in which both groups of students - "online learning sets" and individual students, engage in "online discussion" using a VLE discussion board. We have carried out research at various points in the history of the programme to identify different types of "learners". In order to develop our understanding we have now embarked on a major research programme as part of the SOLSTICE Centre for Excellence for Teaching and Learning, to explore the different dimensions of "online discussion", and the role that both design and tutor intervention has in shaping this discussion. This paper reports on the first stage of this analysis. By studying the postings of four separate learning sets simultaneously following the same ten-week module, it identifies two "active" discussion sets and two comparatively "passive" discussion sets. It also identifies different types of discussion and discussants within these four learning sets. This analysis leads to reflections on the reasons for such different styles of discussion, and identifies opportunities for further research into the relative importance of design and tutoring in promoting online discussion.